1982
DOI: 10.3758/bf03330211
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability and validity of children’s metamemory

Abstract: Test-retest reliability, internal consistency, and construct validity of a metamemory battery were assessed. Fifty-five second-graders were given an extensive metamemory battery on two occasions separated by a 6-week interval. Test-retest correlations ranged from .29 to .49 for individual subtests, with a correlation of .67 for the composite battery. The children were then given training on the use of an interrogative-elaboration strategy to aid paired associate learning. Following three training sessions, tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 6 publications
1
29
0
1
Order By: Relevance
“…Other studies (e.g., Borkowski, Peck, Reid, & Kurtz, 1983;Brown, 1978;Schneider, 1986;Schneideret al, 1986;Weinert et al, 1984) have incorporated some of the items, however, with most of the data consistent with Kreutzer et al's (1975) original fmdings. lt has been established that the items used in the study are generally reliable (Kurtz, Reid, Borkowski, & Cavanaugh, 1982). More recent interview studies are even better from a psychometric perspective, however.…”
Section: Independent Measures: Assessing Knowledge Of Facts About Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies (e.g., Borkowski, Peck, Reid, & Kurtz, 1983;Brown, 1978;Schneider, 1986;Schneideret al, 1986;Weinert et al, 1984) have incorporated some of the items, however, with most of the data consistent with Kreutzer et al's (1975) original fmdings. lt has been established that the items used in the study are generally reliable (Kurtz, Reid, Borkowski, & Cavanaugh, 1982). More recent interview studies are even better from a psychometric perspective, however.…”
Section: Independent Measures: Assessing Knowledge Of Facts About Memorymentioning
confidence: 99%
“…There is convincing evidence of relationships between metamemory, Strategie behaviors and memor from studies that u s w1t atent varia les Hasselhorn, 1986;Kurtz et al, 1982;Schneider, Körkel, & Weinert, 1987b;Weinert et al, 1984;Weinert, Schneider, & Knopf, in press). These analyses permit the conclusions that even relatively young elementary-school children possess knowledge about organizational strategies that has a direct influence on strategic behaviors, which increases the tendency to organize to-be-learned materials taxonomically.…”
Section: Relationships Between Metacognition and Text Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the first four subtests consisted of the assessment of verbalized, declarative knowledge regarding the actions of a hypothetical child, whereas the other two subtests encouraged the child to engage actively in tasks requiring metamemorial judgments. Details of the administration and scoring of these subtests can be found in Kurtz et al (1982). For purposes of the present research, raw scores for each subtest were transformed into standard (Le., "z") scores and summed across subtests for each child.…”
Section: Methodsmentioning
confidence: 99%
“…This article outlines empirical contact points between metamemory and metalinguistic development and their association with general intelligence and achievement. Kurtz, Reid, Borkowski, and Cavanaugh (1982) developed a six-item metamemory battery, assessed its reliability, and demonstrated its validity by showing its relationship with the transfer of an acquired elaborative strategy. Similarly, Ryan and Ledger (1982) showed that metalinguistic knowledge of phonological and syntactic features and of the functions of reading correlate with early reading and sentence-memory performance.…”
mentioning
confidence: 99%